Neuronal and Psychological Underpinnings of Pathological Gambling - Patrick Anselme (Frontiers Research Topics, 2014)
Like in the case of drugs, gambling hijacks reward circuits in a brain which is not prepared to receive such intense stimulation. Dopamine is normally released in response to reward and uncertainty in order to allow animals to stay alive in their environment - where rewards are relatively unpredictable. In this case, behavior is regulated by environmental feedbacks, leading animals to persevere or to give up. In contrast, drugs provide a direct, intense pharmacological stimulation of the dopamine system that operates independently of environmental feedbacks, and hence causes "motivational runaways". With respect to gambling, the confined environment experienced by gamblers favors the emergence of excitatory conditioned cues, so that positive feedbacks take over negative feedbacks. Although drugs and gambling may act differently, their abnormal activation of reward circuitry generates an underestimation of negative consequences and promotes the development of addictive/compulsive behavior. In Parkinson's and Huntington's disease, dopamine-related therapies may disrupt these feedbacks on dopamine signalling, potentially leading to various addictions, including pathological gambling. The goal of this Research Topic is to further our understanding of the neurobiological mechanisms underlying the development of pathological gambling. This eBook contains a cross-disciplinary collection of research and review articles, ranging in scope from animal behavioral models to human imaging studies.